Prolonged Fever and Coronary Artery Involvements: Kawasaki Disease or Systemic Juvenile Idiopathic Arthritis? - Mehrnaz Olfat; Raheleh Assari; Mohamad-Taghi Majnoon; Vahid Ziaee (Reviews in Clinical Medicine, 2023)
Introduction: The symptoms and laboratory findings of Kawasaki disease (KD) and systemic-onset juvenile idiopathic arthritis (SoJIA) may overlap in the early phases. Coronary artery lesions are common complications seen in KD.Cases Presentation: In this article, we report three cases of SoJIA (two males and one female) with prolonged relapsing fever and coronary artery involvement. Initially, all three cases were presumed to have KD and were treated with IVIG. All three cases had arthritis and lymphadenopathy, and one of them had a skin rash. After 3-8 weeks, fever and main clinical symptoms returned. In the second evaluation, they met the criteria for SoJIA and were treated with methylprednisolone, ibuprofen, and methotrexate. High ferritin levels were observed in all three cases (mean=6024 ng/ml).Conclusion: Coronary artery involvement may rarely be seen in the early phases of SoJIA. Continuing or relapsing fever, late-onset arthritis, and increased serum ferritin levels may help distinguish SoJIA from KD.